Spectrum access scheme of MAC layer for real-time traffic in cognitive radio network - Rui-fang LI; Quan LIU; Ren-fa LI (Tongxin xuebao)
These protocols have not satisfied the emergent needs of the increasing real-time businesses and high-level ser-vice quality. In order to satisfy the requirement for real-time transmission of high broadband service in cognitive radio networks, a low-delay spectrum access scheme of MAC layer, LD-SAS, was proposed. In spectrum sensing phase, the transmission delay can be minimized by choosing the optimum available channel number of sensing channels. In channel access contention phase, the effect of channel conflict problem and deaf terminal problem in multichannel coordination can be reduced by designing channel access frame. The theoretical and experimental results were presented to demonstrate the effectiveness of our proposed protocol. Compared with the traditional MAC protocols for cognitive networks, LD-SAS has shorter delay time and slightly better throughput performance when the probability of channel being idle is bigger.